Risk mesurement of cardiovascular disease in family health strategy users - Marcelo Machado Sassi; Gianfábio Pimentel Franco; Sidnei Petroni; Débora Dalegrave; Gabriela de Mattos Nogueira (Universidade Federal de Santa Maria, 2015)
Aim: To quantify the risk on the occurrence of cardiovascular diseases in Family Health Strategy users. Method: quantitative, non-experimental, descriptive and cross-cut time study. For quantification of risk the Framingham General Cardiovascular Disease software was used. Results: 52 subjects were interviewed, 6 of them presented a degree of risk appropriated for their age, 27 had a high level risk for their age and 19 high-risk for their age. Conclusion: risk quantification enables the view on a situation, and thus to draw action plans for intervention